Study on Promotion of the Professional Market Mode and Service Mode in New Economic Times: Take Zhejiang Hai-Gang Intelligent Home City as Example. (September 2020) - Shen, Yuyan; Qian, Yan; Zheng, Xiutian
Abstract: This paper has combined the opportunity of Zhejiang Province to develop modern supply chain, based on the trend of the integration of Internet and professional market in the new economic era, proposed the promotion significance of the professional market similar to the Haigang Intelligent Home City, and then proposedthe business improvement plan of the professional market of the home city, the service mode promotion solution and the time node to realizeon the basis of the analysis of the status quo. It has put forward the new ideas and directions for the transformation and upgrading of the professional market, which has the practical significance and application value.